High resolution imaging of martensitic all-weld metal. (19th May 2017) - Haslberger, P.; Ernst, W.; Schnitzer, R.
ABSTRACT: Martensitic steel welds show promising results regarding their strength while they may tend to be brittle. As martensite is a quite complex microstructure, high resolution techniques like electron backscatter diffraction (EBSD) and atom probe tomography (APT) are valuable tools for an in-depth characterisation. In this study, the average block size and misorientation distribution of martensitic all-weld samples were evaluated with EBSD. A lower carbon content led to a smaller block size and consequently a higher toughness of the all-weld sample. Furthermore, APT revealed a concentration fluctuation of the main alloying elements and particles with a high carbon content. It is discussed how these methods can be used in the future to design the microstructure to achieve optimum properties.